Contribuição ao estudo do peneiramento vibratório operando com redução de pressão na região de secagem da tela - Menezes, Anderson Lima de (2018)
For the reuse of drilling fluid and compliance with environmental constraints, a separation of fluid and solid is required. In the solid treatment unit a vibrating screen is the first equipment, being responsible for the overall efficiency of the system, however several variables influence in its performance. Therefore, the objective of this work was to develop studies on the residual moisture content and the percentage of retained solids in the vibrating screen when subjected to vacuum application in response to variations in g-force, screen inclination and volumetric concentration of solids in the feed. Using a suspension composed by water, xanthan gum, formaldehyde (to simulate the drilling fluid) and standardized sand (to simulate the solids). The experiments were carried out in a 3k factorial design for non-vacum and vacuum screening and were performed in an experimental prototype of a pilot scale vibrating screen with 175 mesh screen and feed rate of 40 kg/min of suspension. The results for the non-vacuum sieving indicated that the minimum residual moisture content was reached with a 3.0 g-force, screen slope of 1.5° and volumetric concentration of 6.0%; while the percentage of retained solids obtained the maximum condition with a 3.0 g-force, screen inclination of 0º and volumetric concentration of 2.0%. On the other hand, the vacuum screen obtained the lowest residual moisture content with a 3.0 g-force, screen inclination of 3.0º and a 6% volumetric concentration; while the highest percentage of retained solids was reached with g-force of 3.0, screen slope of 0° and volumetric concentration of 2.0% equal to the screening without vacuum; and it was also determined the percentage of wet area that obtained the lowest condition with g-force of 5.0, screen slope of 3.0º and volumetric concentration of 6.0%. The optimum operating point considering the lowest residual moisture content, the highest percentage of retained solids and the lowest percentage of wet area was achieved with g-force of 3.0, screen slope of 0.825º and volumetric concentration of 6.0%. The results demonstrated the influence of vacuum on reducing the residual moisture content of the solids retained at the 2.0% concentration. It can be concluded that the results obtained in variation of the g-force, screen inclination and volumetric concentration influence the residual moisture content, the percentage of solids retained and the percentage of area occupied by the liquid (vacuum sieving only). The influence of the vacuum on the drying of the solids was also perceived. In this sense, the study of the variables of this work is important for the understanding of the vibrating sieving in solid-liquid separation under vacuum.